ANTIOKSIDATIF ESTROGEN DALAM MENGHAMBAT ADVANCED OXIDATION PROTEIN PRODUCT AKIBAT REAKSI GLIKOSILASI - Adenan, Adenan; Suhartono, Eko; Setiawan, Bambang (Lembaga Penelitian Universitas YARSI, 2007)
Ethinyl estradiol is an estrogen derivative used as contraceptive or hormone replacement therapy to maintain woman?s sexual function. The aim of this study was to examine ethinyl estradiol antioxidative activity and its potency to inhibit protein oxidation by glycocylation reaction. This study was an in vitro assay and its antioxidative activity by H2O2 scavenging, ?OH scavenging, metal chelating were measured. Activity as inhibitor of Advanced Oxidation Protein Products (AOPP) was carried out by using glycocylation reaction. Three groups (n=6), i.e P0 control (3 ml of serum), P1 (3 ml of serum + glucose 500 mM), and P2 (3 ml of serum + glucose 500 mM + ethinyl estradiol 0,15gr/100mL) were used in this study. The result of this study showed that H2O2 scavenging, ?OH scavenging, metal chelating were 48,889%, 15,139%, 11,538% respectively. For AOPP inhibition, P0 and P1 was different significantly (p 0,05), P0 and P2 was not different significantly (p 0,05), and P1 and P2 was different significantly (p 0,05). It was suggested that antioxidative mechanism from ethinyl estradiol could inhibit AOPP formation generated by glycocylation reaction.